Eco-Innovation, Learning Orientation and Cost Precision: A Strategic Approach to Sustainable Product Design - Dyah Ekaari Sekar Jatiningsih; Jenny Aufa Salsha Belia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study explores the impact of cost information precision, learning orientation, and performance-prove orientation on sustainable product design in the context of ecological innovation and cost efficiency. The method applied in this study is a laboratory experiment with a 2x2x2 factorial design, involving 117 accounting students as participants. The results of the ANOVA test show that each independent variable does not have a significant main effect. However, interestingly, the interaction between cost information precision and performance-prove orientation proved to be significant, indicating that precise cost information is more effective in encouraging sustainable product design when accompanied by motivation to prove performance. These findings confirm that sustainable product design does not only depend on technical factors, but also requires support from cognitive and motivational aspects. This study provides theoretical contributions and practical implications for eco-innovation strategies in facing competition in the industry